Birth of the Cowboy as American Icon - Nathan Bartel (Symphony in the Flint Hills, 2017)
Introduction: Of all the archetypes and folk heroes that populate American culture, none looms larger than the cowboy. And as Flint Hills historian Jim Hoy suggests, "The American cowboy…was born in the dust of the Old Chisholm Trail." [Excerpt from The Chisholm Trail: Driving the American West, a traveling exhibit.]
Keywords: cowboy culture; American frontier; wild west shows; cowboys in film